The "risk-adjusted" price-concentration relationship in banking - III Elijah Brewer; III William E. Jackson (Federal Reserve Bank of Atlanta, 2004)
Price-concentration studies in banking typically find a significant and negative relationship between consumer deposit rates (i.e., prices) and market concentration. This relationship implies that highly concentrated banking markets are "bad" for depositors. It also provides support for the Structure-Conduct-Performance hypothesis and rejects the Efficient-Structure hypothesis. However, these studies have focused almost exclusively on supply-side control variables and have neglected demand-side variables when estimating the reduced form price-concentration relationship. For example, previous studies have not included in their analysis bank-specific risk variables as measures of cross-sectional derived deposit demand. The authors find that when bank-specific risk variables are included in the analysis the magnitude of the relationship between deposit rates and market concentration decreases by over 50 percent. They offer an explanation for these results based on the correlation between a bank's risk profile and the structure of the market in which it operates. These results suggest that it may be necessary to reconsider the well-established assumption that higher market concentration necessarily leads to anticompetitive deposit pricing behavior by commercial banks. This finding has direct implications for the antitrust evaluations of bank merger and acquisition proposals by regulatory agencies. And, in a more general sense, these results suggest that any Structure-Conduct-Performance-based study that does not explicitly consider the possibility of very different risk profiles of the firms analyzed may indeed miss a very important set of explanatory variables. And, thus, the results from those studies may be spurious.
Keywords: 330; Einlagengeschäft; Preismanagement; Unternehmenskonzentration; Struktur-Verhalten-Ergebnis- Paradigma; Bankrisiko; Schätzung; USA